2009
DOI: 10.1007/s00382-009-0638-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil moisture initialisation and lateral boundary conditions on regional climate model simulations of the West African Monsoon

Abstract: In this study, we use the Met Office Hadley Centre regional climate model HadRM3P to investigate the relative impact of initial soil moisture (SM) and lateral boundary conditions (LBC) on simulations of the West African Monsoon. Soil moisture data that are in balance with our particular model are generated using a 10-year (1997-2007) simulation of HadRM3P nested within the NCEP-R2 reanalyses. Three sets of experiments are then performed for six April-October seasons (2000 and 2003-2007) to assess the sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 87 publications
2
29
0
Order By: Relevance
“…At higher temporal resolution, features like the seasonal cycle and the onset of the rainy season are studied to form the basis of a significant assessment of the models performance in simulating these critical characteristics of West Africa climate. The last step investigates projected future climate, with a special emphasis on precipitation, considered as the most difficult parameter to simulate [5] [9] [10] [11]. Statistical methods employed include correlation, variability and error assessments using Taylor diagrams [23], linear regression and coefficient of variation for long-term trends for both historical and projected periods.…”
Section: Investigation Methodsmentioning
confidence: 99%
“…At higher temporal resolution, features like the seasonal cycle and the onset of the rainy season are studied to form the basis of a significant assessment of the models performance in simulating these critical characteristics of West Africa climate. The last step investigates projected future climate, with a special emphasis on precipitation, considered as the most difficult parameter to simulate [5] [9] [10] [11]. Statistical methods employed include correlation, variability and error assessments using Taylor diagrams [23], linear regression and coefficient of variation for long-term trends for both historical and projected periods.…”
Section: Investigation Methodsmentioning
confidence: 99%
“…Gaertner et al [286] found that introducing a soil moisture perturbation into a model had different effects at different scales: a reduction in rainfall over the wet path itself but a net increase in rainfall over a larger area. Moufouma-Okia and Rowell [287], using a regional climate model, found that soil moisture anomalies had little impact on the overall amount of rainfall, creating only small and random intraseasonal, interannual and spatial variations. However, they noted that the conclusion may be model dependent or influenced by the initial soil moisture data introduced into the model.…”
Section: Relationship Between Land-surface Characteristics Andmentioning
confidence: 99%
“…Because of the importance of land surface processes in regional dynamic downscaling, a number of studies have investigated the impact of specification of initial soil moisture and land conditions from data assimilation systems and satellite products (e.g., Pielke et al, 1997;Hong et al, 2009;Moufouma-Okia and Rowell, 2010;Sertel et al, 2010;Panegrossi et al, 2011). Using high resolution soil moisture data derived from ENVISAT/ASAR observations as the initial conditions for the MM5 simulation of the Tanaro flood event of April 2009, the ASAR-derived soil moisture field shows significantly drier conditions compared to the ECMWF analysis and significantly improved the simulation in timing of the onset of the precipitation, as well as the intensity of rainfall and the location of rain/no rain areas (Panegrossi et al, 2011).…”
Section: Specification Of Initial Soil Moisture and Vegetation Conditmentioning
confidence: 99%